(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The information about risk factors for a high stillbirth rate in piglets is inadequate. Therefore, this study was conducted to determine important risk factors for an extremely high stillbirth rate in a commercial pig farm in Vietnam. Materials and Methods: This study included 628 piglets and 45 Landrace × Yorkshire sows. Data including parity number, gestation length (GL), litter size (LS), piglet’s gender, stillbirth, birth order, birth interval (BI), cumulative farrowing duration (CFD), birth weight (BW), crown-rump length (CRL), body mass index, and ponderal index (PI) were collected. To deal with hierarchical data where several piglets might be born from a sow, Generalized Linear Mixed Models (GLMMs) were used to examine the association between stillbirth and investigated risk factors. Results: The stillbirth rate was 14.3%, and the incidence of stillbirth at the litter level was 68.9%. The final multivariate GLMM selected eight factors, including CFD, BI, CRL, BW, PI, GL, LS, and parity, as significant risk factors for stillbirth in the piglet. CFD >90 min, BI > 30 min, CRL 13, and parity 5–8 were associated with increased stillbirth. The final model explained 50.1% of the variation of stillbirth, in which fixed factors explained 43.6% of the variation. Conclusion: The present study indicated that the stillbirth rate in the investigated pig farm was very high, and several factors simultaneously contributed to the situation. Selection for optimal size and shape of piglets, careful supervision of parturition, and replacement of old sows should be some of the practical approaches to reduce the stillbirth rate. J. Adv. Vet. Anim. Res., 9(1): 13–18, March 2022 http://doi.org/10.5455/javar.2022.i564